HRD1‐ERAD controls production of the hepatokine FGF21 through CREBH polyubiquitination. (2nd November 2018) - Wei, Juncheng; Chen, Lu; Li, Fei; Yuan, Yanzhi; Wang, Yajun; Xia, Wanjun; Zhang, Yuehui; Xu, Yuanming; Yang, Zhao; Gao, Beixue; Jin, Chaozhi; Melo‐Cardenas, Johanna; et al.
Abstract: The endoplasmic reticulum‐associated protein degradation (ERAD) is responsible for recognizing and retro‐translocating protein substrates, misfolded or not, from the ER for cytosolic proteasomal degradation. HMG‐CoA Reductase (HMGCR) Degradation protein—HRD1—was initially identified as an E3 ligase critical for ERAD. However, its physiological functions remain largely undefined. Herein, we discovered that hepatic HRD1 expression is induced in the postprandial condition upon mouse refeeding. Mice with liver‐specific HRD1 deletion failed to repress FGF21 production in serum and liver even in the refeeding condition and phenocopy the FGF21 gain‐of‐function mice showing growth retardation, female infertility, and diurnal circadian behavior disruption. HRD1‐ERAD facilitates the degradation of the liver‐specific ER‐tethered transcription factor CREBH to downregulate FGF21 expression. HRD1‐ERAD catalyzes polyubiquitin conjugation onto CREBH at lysine 294 for its proteasomal degradation, bridging a multi‐organ crosstalk in regulating growth, circadian behavior, and female fertility through regulating the CREBH‐FGF21 regulatory axis. Synopsis: Expression of the hepatokine FGF21 is induced by the transcription factor CREBH during fasting. ER‐associated degradation (ERAD) negatively regulates FGF21 levels under fasting‐feeding through CREBH degradation to promote multi‐organ crosstalk, growth, circadian behaviour and fertility in mice. ERAD ubiquitin ligase HRD1 suppresses production of the hepatokine FGF21. HRD1 catalyzes polyubiquitination of transcription factor CREBH. Hepatic HRD1‐ERAD controls growth, circadian behaviour, and female fertility. Deletion of hepatic Fgf21 largely rescues HRD1 deficiency. Abstract : ER quality control pathways promote multi‐organ crosstalk during fasting‐feeding conditions in mice.